2017
DOI: 10.1007/s12275-017-7317-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel methanotroph in the genus Methylomonas that contains a distinct clade of soluble methane monooxygenase

Abstract: Aerobic methane oxidation is a key process in the global carbon cycle that acts as a major sink of methane. In this study, we describe a novel methanotroph designated EMGL16-1 that was isolated from a freshwater lake using the floating filter culture technique. Based on a phylogenetic analysis of 16S rRNA gene sequences, the isolate was found to be closely related to the genus Methylomonas in the family Methylococcaceae of the class Gammaproteobacteria with 94.2-97.4% 16S rRNA gene similarity to Methylomonas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Although growth on pMMO shows better results for methanotrophs in general, sMMO is mainly utilized by Type II only. However, recent studies revealed the ability of some Type I strains to grow under copper‐free conditions . Accordingly, copper was eliminated from the growth medium to study its effect on the dominance, growth rate and the PHB accumulation capacity of the previously enriched type II methanotrophs with similar conditions applied to those during Set‐3 experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although growth on pMMO shows better results for methanotrophs in general, sMMO is mainly utilized by Type II only. However, recent studies revealed the ability of some Type I strains to grow under copper‐free conditions . Accordingly, copper was eliminated from the growth medium to study its effect on the dominance, growth rate and the PHB accumulation capacity of the previously enriched type II methanotrophs with similar conditions applied to those during Set‐3 experiments.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies revealed the ability of some Type I strains to grow under copper-free conditions. 26 Accordingly, copper was eliminated from the growth medium to study its effect on the dominance, growth rate and the PHB accumulation capacity of the previously enriched type II methanotrophs with similar conditions applied to those during Set-3 experiments. Table 1 shows a comparison between all the conditions applied towards achieving stable type II enrichment with high PHB accumulation production throughout this study.…”
Section: Cultivation In Copper-free Medium and Switching The Nitrogenmentioning
confidence: 99%
“…Morphological observations were made using cells grown on methane. Cells of exponentially growing cultures of strain IM1 T were harvested by centrifugation and sent for transmission electron microscopy analyses at the Korean Basic Science Institute, Ochang Centre, Republic of Korea, as previously described [25]. To demonstrate the presence of flagella, cells were negatively stained with 1 % (w/v) phosphotungstic acid solution and visualized using a JEM-1400 Plus transmission electron microscope (jeol) at an accelerating voltage of 120 kV.…”
Section: Morphological Characteristicsmentioning
confidence: 99%
“…Evaluation of the pH range for growth was achieved with LSM medium containing 5 mM Homo-PIPES for pH 4.0 to 5.0, 1 mM phosphate buffer (pH 5.5-8.0) and 10 mM carbonate-bicarbonate buffer (pH 9.0-10.0). Additionally, the ranges of salt tolerance (0-3 %, w/v, at every 0.5 % interval) and growth temperature (6,10,20,25,30,37,42,45,48, 50 and 55 °C) of strain IM1 T were evaluated.…”
Section: Growth Experimentsmentioning
confidence: 99%
“…Strain FJG1 contains the operons pmoCAB and pxmABC , which encode particulate methane monooxygenase (pMMO) and copper-containing membrane monooxygenase ( 12 ). However, the soluble methane monooxygenase operon ( mmoXYBZDCGR ) ( 13 ) is not present. The genome also contains genes encoding cyanoglobins ( hbN ), one of which is upregulated under hypoxic conditions and hypothesized to bind oxygen for delivery to pMMO ( 6 ).…”
Section: Genome Announcementmentioning
confidence: 99%